2015
DOI: 10.1080/17442508.2015.1124878
|View full text |Cite
|
Sign up to set email alerts
|

Enlargement of filtration and predictable representation property for semi-martingales

Abstract: We present two examples of loss of the predictable representation property for semi-martingales by enlargement of the reference filtration. First of all we show that the predictable representation property for a semi-martingale X does not transfer from the reference filtration F to a larger filtration G if the information starts growing up to a positive time. Then we study the case G = F ∨ H when there exists a second special semi-martingale Y enjoying the predictable representation property with respect to H.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Proof. i1) This statement is the extension to the multidimensional case of Lemma 4.2 in [6]. Thanks to point i) of Lemma 3.1 its proof is exactly the same.…”
Section: Two Bases Of Martingalesmentioning
confidence: 69%
See 1 more Smart Citation
“…Proof. i1) This statement is the extension to the multidimensional case of Lemma 4.2 in [6]. Thanks to point i) of Lemma 3.1 its proof is exactly the same.…”
Section: Two Bases Of Martingalesmentioning
confidence: 69%
“…When X and Y are not trivial semi-martingales, that is when they do not coincide with M and N respectively, under suitable assumptions, we are able to prove that the representation is the same. We stress that the approach is slightly different from that used to handle the unidimensional case (see Section 4.2 in [6]) and also that the hypotheses are simpler than those required in that paper. Here the question reduces to ask for conditions under which the (P X , F)-p.r.p.…”
Section: Introductionmentioning
confidence: 92%
“…In Section 3, we establish the main results of the present paper, Theorem 3.6 below, about the propagation of the WRP and the PRP. Section 4 is devoted to the study of the orthogonality of the fundamental martingales which are used for the martingale representation in G. In particular, as a consequence of Theorem 3.6, we generalize the results obtained in [4] on the martingale representation to the case of a non-trivial initial filtration in the context of point processes. In the appendix we discuss a lemma which will be useful to study the orthogonality of the involved martingales.…”
Section: Introductionmentioning
confidence: 98%
“…In [4] it is also shown that the multiplicity of G is, in general, equal to three. In [5], the results of [4] are generalized to multidimensional martingales M and N.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation